Bankruptcy risk assessment of JSC Ukrtelecom - LAZORENKO, L.; NIKIFOROV, M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The current stage of economic development requires enterprises to constantly improve the efficiency of activities and strengthen their positions. The introduction of a bankruptcy risk assessment system of any enterprise is an integral condition for its successful operation. The issue of applying appropriate methods and models for assessing the risk of bankruptcy of enterprises and developing ways to overcome or prevent them in order to improve the efficiency of enterprises is especially relevant in the current conditions. The purpose of the study is assessing the bankruptcy risk of JSC Ukrtelecom and determining the ways to overcome and prevent it. One of the most important methods of the early warning system and the method of forecasting the bankruptcy of enterprises is discriminant analysis. The most famous model of one-factor discriminant analysis is Beaver’s system. In the practice of financial and economic activities of western firms, the five-factor Altman model is widely used to assess the risk of bankruptcy. The possibility of overcoming and preventing the risk of bankruptcy should be considered in conceptual and practical contexts. Today, the sphere of telecommunication services is quite developed and is highly efficient. But some enterprises in this industry still need constant monitoring and improvement of activities, since due to high competition they become unprofitable due to the use of outdated technologies or lack of demand for services. One of these enterprises is JSC Ukrtelecom, which in 2022 is unprofitable. According to the assessment of the risk of bankruptcy of JSC Ukrtelecom by three models, it is low and amounts to 15–20%. it is advisable to implement the following measures: attracting additional funds to restore the profitability of the enterprise; restructuring of debt obligations of the enterprise; revision and change of the pricing policy of the enterprise; changing the range of services provided by the enterprise; improving the technological component of service provision.